A Clinical Evaluation of Routine Blood Sampling Practices in Patients With Diabetes: Impact on Fingerstick Blood Volume and Pain. (July 2014) - Grady, Mike; Pineau, Mitchel; Pynes, Mary Kate; Katz, Laurence B.; Ginsberg, Barry
Background: There is a perception that patients with diabetes struggle to produce sufficient blood to fill glucose test strips, including strips with 1-µL fill requirements. The purpose of this study was to determine the volume of blood expressed when these patients perform routine fingersticks using their own lancing device and sampling technique and to evaluate the relationship between blood volume and pain. Methods: Sixty-four patients (type 1 or type 2 diabetes) performed 8 fingersticks using their own lancing device and preferred depth setting and lancing technique. Eight different commercially available lancing systems were used (8 patients/system). Blood volume and perceived pain were recorded after each fingerstick. Results: The mean blood volume across all patients was 3.1 µL (512 fingersticks), with 97% of patients expressing a mean of ≥1.0 µL of blood. There was no correlation between pain response and the volume of blood expressed. Nearly all patients agreed that they could easily and comfortably obtain a 1-µL blood sample, and most patients actually preferred a larger drop size to ease sampling and avoid wasting strips. Conclusion: These results provide evidence across 8 lancing systems that challenge the current perceptions that patients with diabetes struggle to produce sufficient blood samples to fill most test strips, including those with 1-µL fill requirements, and that obtaining larger volumes of blood is more painful. These results are consistent with the previous literature suggesting that patients derive no real benefits from very low strip volumes and generally prefer a blood drop size that enables them to confidently fill their test strip.